2017
DOI: 10.1002/2017rs006331
|View full text |Cite
|
Sign up to set email alerts
|

Distributed sensing of ionospheric irregularities with a GNSS receiver array

Abstract: We present analysis methods for studying the structuring and motion of ionospheric irregularities at the subkilometer scale sizes that produce L band scintillations. Spaced‐receiver methods are used for Global Navigation Satellite System (GNSS) receivers' phase measurements over approximately subkilometer to kilometer length baselines for the first time. The quantities estimated by these techniques are plasma drift velocity, diffraction anisotropy magnitude and orientation, and characteristic velocity. Uncerta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…It is worth mentioning that the work presented in Wang and Morton () and this paper are in parallel with Su et al (). Both studies address the ionospheric drift velocity remote sensing problem using receiver arrays at a similar location.…”
Section: Introductionsupporting
confidence: 73%
“…It is worth mentioning that the work presented in Wang and Morton () and this paper are in parallel with Su et al (). Both studies address the ionospheric drift velocity remote sensing problem using receiver arrays at a similar location.…”
Section: Introductionsupporting
confidence: 73%
“…PFISR measurements on 8 December 2013 of (a) electron density, (b) electron temperature, and (c) ion temperature over altitude and time. From 03:43 to 04:17 UT an L1 phase scintillation event was identified by Su, Datta‐Barua, et al (). PFISR measurements on 7 October 2015 of (d) electron density, (e) electron temperature, and (f) ion temperature over altitude and time.…”
Section: Methodsmentioning
confidence: 99%
“…We use two case studies in the literature (Semeter et al, ; Su, Datta‐Barua, et al, ) to help determine which PFISR data parameter, density, or ion or electron temperature, is a reasonable single indicator of the layer correlated with the GPS scintillations. The first case study from the literature is an F‐region scintillation on 8 December 2013 (Datta‐Barua et al, ; Su, Datta‐Barua, et al, ). According to those studies, the peak electron densities and the highest electron temperature were observed to occur in the F‐region altitudes at the same time during which the scintillation had occurred, from about 03:43 to 04:17 UT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their compact, low cost, and distributive nature, GPS receivers became increasingly popular in this research area (Basu et al, ; Kil et al, , ; Kintner et al, ). With the modernization of Global Navigation Satellite System (GNSS), high‐rate multi‐GNSS carrier phase signals have been utilized in high‐latitude regions (Su et al, ; Wang et al, ; Wang & Morton, , ). The gist of the technique is to find the time delay between receiver measurements through cross correlation when similar diffraction pattern is observed on different receivers.…”
Section: Introductionmentioning
confidence: 99%